Can Sharia Financial Literacy in Microfinance Customers Increase the Understanding of BPRS Haji Miskin KC Payakumbuh Customers - Riski Murdani; Aidil Alfin; Awaluddin Awaluddin (Universitas 17 Agustus 1945 Semarang, 2024)
The main objective of this study is to fill the knowledge gap in Islamic financial literacy experienced by microfinance customers by identifying their experiences in implementing these practices, the challenges they face and the opportunities that exist. Although this research is qualitative descriptive, this research includes field research. Primary and secondary sources of information were used to compile the results of this study. Research Methods This research uses a qualitative method with a descriptive approach, carried out at BPRS Haji Miskin KC Payakumbuh, identifying both internally and externally so that it can analyze what is currently an obstacle to customer understanding in Islamic financial literacy in murabahah financing products and describe the developments that can be done to improve customer Islamic financial literacy in murabahah financing products.The results of the research The understanding of financing customers is based on the findings of this micro-research that increases in following Islamic financial literacy, increasing customer insights, so customers can distinguish Islamic finance from conventional finance. The obstacles and risks faced by microfinance customers of BPRS Haji Miskin KC Payakumbuh in Islamic financial literacy are that most of the microfinance customers cannot participate in the Islamic finance education program because the distance to the customer's home and the location of the Islamic finance education is very far because the program is carried out at the head office.